Predicting Changes in the Land Use in Midsize Cities (Case Study: Urmia City of Iran in 2025) - Basiri, Mostafa; Someh, Mina Farokhi (International Journal of Geography and Geology, 2015)
The Urmia is the capital city of the Western Azerbaijan province that is an urban area and in the northwest of Iran. In recent years, the rapid increase in urban lands and areas in this city has resulted in inconsistent and extensive urban growth. The purpose of the present study is to predict the changes in the land use in midsize cities and apply this prediction on the case study of the Urmia city in Western Azerbaijan. Satellite images and IDRISI Andes have investigated the changes land use in the lands of Urmia city and were used GIS to examine the land use and changes from 1984 to 2011. Then, Markov Chain model and Cellular automate have been used in IDRISI Andes to document and propose a prospect of land use changes in the Urmia city in 2025. With respect to the land use changes, the results of the present study will indicate that the built up area in this city in 1984 was about 2706.57hectares; however, in 2011, the area of built urban zones in the same city has reached 9811.26 hectares. Hence, in 2025, it can be speculated that in the future, the area of built up will reach 12970.53 and the agricultural lands will inevitably be allocated for urban constructions; that is, in 2025, all agricultural lands will undergo a change of land use from farming into urbanization. It should be pointed out that due to the population growth in this area and the available lands, a 3000-hectare increase in the area will be needed to accommodate the increased population.